Креативна дискурсивна особистість англомовного політика - Морозова, Анна Олегівна; Morozova, A. O. (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Актуальність дослідження цієї наукової розвідки полягає в еколінгвістичному дослідженні дискурсу креативних англомовних особистостей у світовій політиці, з урахуванням вербальних і невербальних аспектів. … Наукова новизна роботи полягає в еколінгвістичному підході до вивчення креативності у комунікації англомовних політиків.

This thesis investigates the ecolinguistic features of verbal and non-verbal communication that shape the creative discursive personality of an English-speaking politician. This focus accounts for the relevance of the study for the present-day linguistics. The ecolinguistic approach to the analysis of political discourse provides new insights into how language reflects and shapes the ecological balance of communication in society. The discourse of English-speaking politicians has been examined through the implementation of the functional, communicative, and ecolinguistic approaches to the analysis of verbal and non-verbal interactions of political figures in various communicative situations, which reveal their creativity as discursive personalities.
The creative discursive personality of an english-speaking politician
Керівник роботи: Шпак Олена Владиславівна, кандидат філологічних наук, доцент, кафедра англійської філології та методики викладання іноземної мови
Keywords: HUMANITIES and RELIGION; англомовний політик; дискурс; дискурсивна особистість; еколінгвістика; креативна дискурсивна особистість; english-speaking politician; discourse; discursive personality; ecolinguistics; creative discursive personality